An Optimisation Approach Toward Onboard Energy Management Systems: Modelling And Simulation Of Supply Side - Suroso, Hadi; Penangsang, Ontoseno (Jurnal Teknik Industri, 2010)
Optimization in the operation of electric power system is an important task for both in land and onboard. The objective is to minimize operating cost index. Taking advantage of the scheme that onboard operator has the authority not only in the supply side but also in the demand side, an optimization approach toward onboard energy management systems based on integrated model for supply and demand side is being developed. The model utilizes unit commitment and economic dispatch in the supply side and load management based on multiple attribute decision-making in the demand side. As a part of the whole concept, this paper focuses on the modeling and simulation of demand side. A user friendly demand side model consisting of Unit Commitment and Economic Dispatch is developed by using LabVIEW, Laboratory Virtual Instrument Engineering Workbench. Data taken from 3 units of Steam Power Plant are simulated. It is then eventually confirmed that 9% total cost saving can be achieved in the selected load demand range